2005
DOI: 10.1007/s10611-005-3003-1
|View full text |Cite
|
Sign up to set email alerts
|

‘Blue walls,’ ‘grey areas’ and ‘cleanups’: Issues in the control of police corruption in England and Wales

Abstract: This paper examines issues concerned with police corruption and its control in England and Wales. The topic of defining police corruption is addressed, some current areas of risk are described and anti-corruption strategies, particularly those pursued by the London Metropolitan Police Service (MPS), are examined. What appears qualitatively and quantitatively different in the approach of services such as the MPS and Merseyside Police is the use of an adequately resourced, dedicated anti-corruption unit. This st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…A 1998 American report submitted by the General Accounting Office, which studied drug related police corruption, stated that police enforcing laws against all forms of vice were open to opportunities for corruption. Both Dunnighan and Norris (1998) and Moran (2005) also provided support for the factor of 'opportunity'. Dunnighan and Norris (1998) reported that the majority of officers see rule bending as an essential component of running informers.…”
Section: Why Do Officers Commit Police Deviance?mentioning
confidence: 99%
See 1 more Smart Citation
“…A 1998 American report submitted by the General Accounting Office, which studied drug related police corruption, stated that police enforcing laws against all forms of vice were open to opportunities for corruption. Both Dunnighan and Norris (1998) and Moran (2005) also provided support for the factor of 'opportunity'. Dunnighan and Norris (1998) reported that the majority of officers see rule bending as an essential component of running informers.…”
Section: Why Do Officers Commit Police Deviance?mentioning
confidence: 99%
“…Dunnighan and Norris (1998) reported that the majority of officers see rule bending as an essential component of running informers. Moran (2005) stated that opportunities for corruption are continuously provided in certain areas of policing due to context. He proposed that the specific context of certain activities, combined with the policing of those activities and the development of criminal groups, historically provides for the development of certain forms of police corruption.…”
Section: Why Do Officers Commit Police Deviance?mentioning
confidence: 99%
“…Consequently, this informs the context and pervading culture within which the present study was conducted. Exploring police corruption is empirically socially different from other professions (Moran, 2005), and a qualitative inquiry appears to engender more effective illumination of the issues underpinning police corruption. As most indicators of corruption in the police force are subjective indicators (Lambsdorff, 2006) the research orientation therefore needs to discriminate more effectively the various issues (Hill, Thompson & Williams, 1997;Walsh, White & Young, 2008).…”
Section: Methodsmentioning
confidence: 93%
“…Consequently, utilising policing surveys (Ede & Legosz, 2002) does very little as they project unsupported and unsubstantiated opinion lacking in authoritive scope, reliability and significance (Klockars, et al, 2000). Further, the literature neglects to research the application of the organisational injustice concept (Trinkner, Tyler & Goff, 2016) nor social learning theory (Chappell & Piquero, 2004) to help illuminate the level and prevalence of police misconduct (Moran, 2005;Brown, 2006). However, much research cannot be done effectively because of demonstrated lack of access under the notion of "security" to real data collected by police during their inquiries and the application of internal decision-making processes (Kane, 2002).…”
Section: Journal Of Public Administration and Governancementioning
confidence: 99%
“…Research on criminal networks is well established in the criminology literature but has received minimal consideration from a social network theoretical approach, and few studies have done so on an empirical basis (Moran, 2005;Morselli & Tremblay, 2004). Accordingly, this thesis makes numerous theoretical and practical contributions.…”
Section: Research Contributionsmentioning
confidence: 99%